LOCAL FOOD MSME DIGITAL MARKETING STRATEGY (CASE STUDY IN BANDA ACEH CITY) - Putri Diary; T. Saiful Bahri; Fajri (CV. Radja Publika, 2023)
Marketing activities or promotional activities for a product (brand or brand) that are carried out digitally with the aim of reaching as many customers as possible in a relevant, effective and efficient way are called digital marketing. This study aims to: (1) determinants in determining the digital marketing strategy for MSME local food products in the city of Banda Aceh. (2) the right strategy and become a priority alternative to increase digital marketing for MSMEs of local food products in the city of Banda Aceh. The aims of this research are: (1) IFE and EFE Matrix (2) Strength-Weakness-Opportunity-Threat (SWOT) Matrix (3) Quantitative Strategic Planning Matrix (QSPM). The results of the evaluation of internal factors (IFE) obtained a value of 2.98 and external factors (EFE) obtained a value of 2.73. Based on the internal-external (IE) matrix, The position of internal and external factors that determine the digital marketing strategy for local food MSMEs in Banda Aceh City are in quadrant V (Stability), namely conditions that are relatively good or stable at present and have prospects for the future. Meanwhile, based on the SWOT matrix, the results show that the position of local food MSME business development factors in the city of Banda Aceh related to digital marketing strategy is in quadrant I, namely expansion. So, in this position the right strategy to be implemented by local food MSMEs in Banda Aceh City is the SO (strength-opportunity) strategy, namely utilizing strengths to maximize opportunities, by developing businesses through online marketing media, as well as maximizing the convenience of digital transactions and taking advantage of promotional opportunities as well as increasing cooperation in digital product promotion with third parties. Based on the QSPM matrix ranking, the results of the strategy